2014
DOI: 10.1073/pnas.1402106111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of ApoE and ApoER2 differentially modulate endothelial function

Abstract: It is poorly understood why there is greater cardiovascular disease risk associated with the apolipoprotein E4 (apoE) allele vs. apoE3, and also greater risk with the LRP8/apolipoprotein E receptor 2 (ApoER2) variant ApoER2-R952Q. Little is known about the function of the apoE-ApoER2 tandem outside of the central nervous system. We now report that in endothelial cells apoE3 binding to ApoER2 stimulates endothelial NO synthase (eNOS) and endothelial cell migration, and it also attenuates monocyte-endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
(45 reference statements)
2
52
0
Order By: Relevance
“…In that manner the current findings extend our understanding of the biology of apoER2 beyond its well-established role in CNS development and Alzheimer’s disease (30) and its recently revealed functions in endothelium (26;29). Immunohistochemical analysis of human placenta revealed that apoER2 is abundantly expressed in trophoblasts throughout gestation, and immunoblotting demonstrated that the receptor is also expressed in HTR-8/SVneo and SW.71 cells that retain the characteristics of trophoblasts in culture (33;34;36).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In that manner the current findings extend our understanding of the biology of apoER2 beyond its well-established role in CNS development and Alzheimer’s disease (30) and its recently revealed functions in endothelium (26;29). Immunohistochemical analysis of human placenta revealed that apoER2 is abundantly expressed in trophoblasts throughout gestation, and immunoblotting demonstrated that the receptor is also expressed in HTR-8/SVneo and SW.71 cells that retain the characteristics of trophoblasts in culture (33;34;36).…”
Section: Discussionsupporting
confidence: 60%
“…In another recent study we discovered that apoER2 in endothelium also mediate responses to apolipoprotein E3 that are beneficial to cardiovascular health (29), highlighting the complexities of apoER2 function even in a single cell type. The biology of apoER2 is best understood in neurons in which it is critically involved in central nervous system development and Alzheimer’s disease (30).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lrp8 is also involved in other physiologically processes, e.g. lipid-raft sorting, endothelial cell migration and fetal growth [51,52]. In addition, Yao et al .…”
Section: Discussionmentioning
confidence: 99%
“…23, 24, 3437 To explore the importance of endothelial ApoER2 for APC’s cytoprotective actions, we used EA.hy926 cells as an endothelial cell surrogate 38, 39 to study some of APC’s various activities. Extensive data in this report show that ApoER2 is required for APC’s cytoprotective and signaling activities in this cell line.…”
Section: Discussionmentioning
confidence: 99%